Inflammation, underweight, malignancy and a marked catabolic state as predictors for worse outcomes in COVID-19 patients with moderate-to-severe disease admitted to Internal Medicine Unit. - Valeria Guglielmi; Luca Colangeli; Valeria Scipione; Simona Ballacci; Martina Di Stefano; Lauren Hauser; Michela Colella Bisogno; Monica D'Adamo; Emanuela Medda; Paolo Sbraccia (PLoS ONE, 2022)
Introduction During COVID-19 pandemic, Internal Medicine Units (IMUs) accounted for about 70% of patients hospitalized. Although a large body of data has been published regarding the so-called first wave of the pandemic, little is known about the characteristics and predictors of worse outcomes of patients managed in IMUs during the second wave. Methods We prospectively assessed demographics, comorbidities, treatment and outcomes, including ventilation support (VS) and death, in patients admitted to our IMU for SARS-CoV-2 between October 13th, 2020 and January 21st, 2021. Clinical evolution and biochemical testing 1, 7 and 14 days after COVID-19 diagnosis were recorded. Results We studied 120 patients (M/F 56/64, age 71±14.5 years) admitted to our IMU. Most of them had at least one comorbidity (80%). Patients who died were older, more frequently underweight, affected by malignant neoplasms and on statin therapy compared to patients eventually discharged. Both worse outcome groups (VS and death) presented higher neutrophils, ferritin, IL-6 and lower total proteins levels than controls. Age was significantly associated with mortality but not with VS need. The multivariate analysis showed age and gender independent association of mortality with underweight, malignancy and antibiotics use at the admission. With regard to biochemical parameters, both unfavourable outcomes were positively associated with high WBC count, neutrophils, blood urea nitrogen and low serum total proteins. Conclusions Our study identified inflammation, underweight, malignancy and a marked catabolic state as the main predictors for worse outcomes in COVID-19 patients admitted to IMU during the so-called second wave of the pandemic.